Kebijakan Pentashihan Aplikasi Al-Qur’an Digital di Indonesia: Studi Perkembangan Aplikasi “Al-Quran Kementerian Agama” dan Permasalahannya - Debi Ayu Puspitasari (J-PAI: Jurnal Pendidikan Agama Islam, 2022)
This study aims to conduct a theoretical study related to regulations and provisions in supervising the development of digital Al-Quran applications, as well as the development of the Ministry of Religion's Qur'an applications and their problems. The research method used in this research is descriptive-analytical, to explore and examine data with social analysis theory as well as map and analyze the data and the reality in it so that a descriptive picture of a Qur'anic tradition in the present day can be seen. The results of this study indicate that the Ministry of Religion's Qur'an application developed by LPMQ cannot stem the existence of other applications containing the Digital Qur'an, so there is a need for guidelines and technical guidelines related to making digital Al-Quran applications. The Ministry of Religion's Qur'an application on the Appstore application shows that there are several reviews regarding the Ministry of Religion's Qur'an application that need attention and improvement so that periodic improvements need to be made to maintain the quality of the Ministry of Religion's Qur'an application both in terms of content and operating system.